Radiation risk management when handling radioactive substances and materials - Mamontov, O.V.; Malyk, B.O.; Tokarieva, О.V. (Вопросы атомной науки и техники, 2021)
The system of personnel protection from ionizing radiation in laboratories and industrial premises, where they work with radioactive substances and materials has been considered. A logical scheme in the form of a tree of failures and mathematical expressions for calculating the reliability of the protection system are presented. The coefficients of the influence of individual elements on the reliability of the system are determined. A quantitative analysis of the coefficients of influence made it possible to identify the most significant and most unreliable elements (“weak links”). In order to replace the “weak links”, a list of alternative elements and possible combinations of elements in the protection system has been compiled. Two risk management strategies are proposed. The first strategy involves minimizing the likelihood of failure of the protection system. The second is to minimize the cost of its operation. The possibility of achieving a positive effect has been demonstrated in both cases.